Paternity testing requested by private parties in Italy: some ethical considerations. Issue 10 (30th September 2008) - Caenazzo, L; Comacchio, A; Tozzo, P; Rodriguez, D; Benciolini, P
Abstract : In Italy, judicial and extrajudicial requests for paternity testing have increased in recent years. A retrospective analysis of such private extrajudicial requests received by the legal medicine unit of the Department of Environmental Medicine and Public Health of Padua University was conducted to identify problem areas most helpful in determining whether to accept private parties' requests for paternity testing. Such testing is most delicate when a presumptive father may be seeking to disown paternity and when testing is wanted without the consent of a member of the mother–child–father triangle. Tests that could establish paternity where none has been recognised are less problematic, as the child will not lose out. Legal and ethical–deontological aspects of consent, of the protection of minors and of children's and parents' need for follow-up interviews to deal with the outcome of such testing are carefully considered by the Padua University team when deciding whether to accept a request for testing. It is argued that because such issues are not dealt with by mail-order laboratories, the use of such services is inappropriate.